Effect of extracorporeal hemoadsorption in critically ill patients with COVID-19: A narrative review - Chang, Kaixi; Li, Yupei; Qin, Zheng; Zhang, Zhuyun; Wang, Liya; Yang, Qinbo; Geng, Jiwen; Deng, Ningyue; Chen, Shanshan; Su, Baihai (Frontiers in Immunology, 2023)
COVID-19 has been affecting the world unprecedentedly and will remain widely prevalent due to its elusive pathophysiological mechanism and the continuous emergence of new variants. Critically ill patients with COVID-19 are commonly associated with cytokine storm, multiple organ dysfunction, and high mortality. To date, growing evidence has shown that extracorporeal hemoadsorption can exert its adjuvant effect to standard care by regulating immune homeostasis, reducing viremia, and decreasing endotoxin activity in critically ill COVID-19 cases. However, the selection of various hemofilters, timing of initiation and termination of hemoadsorption therapy, anticoagulation management of extracorporeal circuits, identification of target subgroups, and ultimate survival benefit remain controversial. The purpose of this review is to comprehensively summarize the rationale for the use of hemoadsorption in critically ill patients with COVID-19 and to gather the latest clinical evidence in this field.